MICROBIOTA AND HUMAN HEALTH: BIOLOGICAL MECHANISMS AND CLINICAL IMPACT (European Science Methodical Journal, 2026)
The human microbiota represents a complex and dynamic ecosystem composed of trillions of microorganisms, including bacteria, viruses, fungi, and archaea, that colonize various anatomical sites of the body. Among these, the gut microbiota has emerged as a central regulator of host physiology, metabolism, immune function, and neurobehavioral processes. Advances in high-throughput sequencing technologies and metagenomic analysis have significantly expanded our understanding of host–microbiota interactions and their role in maintaining health and contributing to disease pathogenesis. The biological mechanisms through which microbiota influence human health include modulation of immune system development, production of bioactive metabolites such as short-chain fatty acids (SCFAs), regulation of epithelial barrier integrity, and interaction with endocrine and neural signaling pathways. Dysbiosis—an imbalance in microbial composition and function—has been strongly associated with a wide range of diseases, including inflammatory bowel disease, obesity, metabolic syndrome, type 2 diabetes, cardiovascular diseases, autoimmune disorders, neurodegenerative conditions, and certain cancers.Recent clinical research highlights the therapeutic potential of microbiota-targeted interventions such as probiotics, prebiotics, synbiotics, dietary modulation, and fecal microbiota transplantation (FMT). Personalized microbiome-based medicine is emerging as a promising approach for disease prevention and treatment.This article provides a comprehensive analysis of the biological mechanisms underlying microbiota-host interactions and evaluates their clinical implications in modern medicine. Understanding the microbiome as a key regulatory system offers new perspectives for translational research and precision healthcare strategies.